Monitoring air pollutant index (API) using Aeroqual AQM 65 @ UMP, Kuala Pahang, Pekan - Chin, Yan Yee (2019)
With air pollution have become increasingly prominent, the public increasingly concerned about urban air quality problems, when most cities have begun to study the air quality monitoring, and air quality auto-monitoring system that automatically came into being. In this research, we will specifically study the ambient air quality monitoring at a peat swamp area since the burning of peat swamp forests often causes air pollution. Without air, living things will die. Without clean air, living things will suffer from severe diseases. The status of air quality is very important and is being monitored all day long. In Malaysia, the Department of Environment (DOE) monitors the country’s ambient air quality through air quality monitoring stations. These monitoring stations are strategically located in different areas, typically the residential, traffic and industrial areas to detect any significant change in the air quality which may harm human’s health and the environment. The objective of this study is to monitor the Air Pollutant Index using real time air monitoring at a peat swamp area. Through this study, the air pollution assessments in Kuala Pahang, Pekan for future pollution control strategies can also be determined. The pollutant concentrations in the peat swamp area can be investigated and collected too. The method used in this research is API Status Indicator can be calculated from the data obtained from Aeroqual Cloud, an online software specifically connected to the Aeroqual AQM 65. API, known as Air Pollutant Index is an indicator developed based on scientific assessment to indicate in an easily understood manner, the presence of pollutants and its impact on health to human beings and the environment. A Guide to Air Pollutant Index (API) in Malaysia is referred to as handbook. The data obtained starts from March 2018 till March 2019 which spans about 13 months. Analysis shows that the air monitoring station at Kuala Pahang, Pekan shows the highest value of API reading with 235.2 on the 3rd March 2019 (very unhealthy level), where on that day Malaysia probably faced its worst air quality due to haze episodes. Over the 13 months, API value has the highest frequency at good and moderate levels, which is mostly at 83% to 100%. API value reading is vital for determining the status of air quality on that particular day. The worst quality of air can harm human health, the environment, and also economic development. From the API reading obtained, the government can take action to reduce the worst air quality by taking suitable pollution control strategies.